PENGAWASAN OPERASIPONAL TEMPAT HIBURAN BILYARD DI KOTA PEKANBARU - DELVI ADRIE; ERNAWATI " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Supervision of Operational PlacesinPekanbaru citybilliard Entertainment. Still many entertainment places operational billiard in the city of Pekanbaru that does not comply with the rules in force behind this study. The purpose of this study is to determine the operational supervision billiard entertainment venues in the city of Pekanbaru, and what factors are used effects of operational supervision billiard entertainment venues in the city of Pekanbaru.Theoretical concepts that researchers use is the management and supervision. This study used qualitative research methods to the assessment of descriptive data. In collecting the data, the researcher used interview techniques, observation and literature. By using key informant and the informant as a supplementary source of information.The results of this study show that not optimal operational supervision billiard entertainment venues in the city of Pekanbaru the Civil Service Police Unit conducted ofPekanbaruby way of monitoring, conduct training, and take action. There is still its affecting factors in terms of both internal and external.Keywords: Billiard Entertainment, Operational, Supervision